The Apocalypse of Abraham in its ancient and medieval contexts - Paulsen-Reed, Amy (The Brill reference library of ancient Judaism, 2021)
"The Apocalypse of Abraham is a pseudepigraphal work that narrates Abraham's rejection of idol worship and his subsequent ascent to heaven, where he is shown eschatological secrets through angelic mediation. This fascinating text was only preserved in Old Church Slavonic and must be studied as both a medieval Christian and an ancient Jewish text. This monograph addresses the following questions: -Why were medieval Slavs translating and reading Jewish pseudepigrapha -How much, if at all, did they emend or edit the Apocalypse of Abraham? -When in antiquity was it most likely written? -What were its ancient Jewish social and theological contexts?"--